Effect of pilates method on water and solo pilates on muscle strength and balance in sedentary old women (Revista Brasileira Multidisciplinar, 2022)
Introduction: In view of the aging scenario, effective methods are needed to improve strength and balance, providing a better quality of life for this population. Objective: To evaluate the effect of the Pilates method in Water and Pilates Mat on muscle strength and balance in sedentary elderly women. Materials and methods: Strength was assessed using a dynamometer and balance using the Berg Balance Scale. The pilates water and pilates solo groups performed 16 sessions and the control group did not receive interventions. Muscle strength and balance were assessed before and after the exercise program. Results: The sample included 32 elderly women divided into groups: pilates water (n =11), pilates floor (n =11) and control (n=10). There was no statistically significant difference between the pre and post comparisons of each group, as well as in the intergroup analysis. When comparing the results referring to the pre and post balance of each group, it was possible to verify that there was a difference in the Water Pilates group, which did not occur in the Mat Pilates group. Conclusion: The Pilates method in water proved to be more effective in balancing sedentary elderly women.
Keywords: Muscle strength; Balance; Elderly; Sedentary Behavior; Exercise and Movement Techniques